Insight into the Web of Stress Responses Triggered at Gene Expression Level by Porphyrin-PDT in HT29 Human Colon Carcinoma Cells - Maria Dobre; Rica Boscencu; Ionela Victoria Neagoe; Mihaela Surcel; Elena Milanesi; Gina Manda (MDPI AG, 2021)
Photodynamic therapy (PDT), a highly targeted therapy with acceptable side effects, has emerged as a promising therapeutic option in oncologic pathology. One of the issues that needs to be addressed is related to the complex network of cellular responses developed by tumor cells in response to PDT. In this context, this study aims to characterize in vitro the stressors and the corresponding cellular responses triggered by PDT in the human colon carcinoma HT29 cell line, using a new asymmetric porphyrin derivative (P2.2) as a photosensitizer. Besides investigating the ability of P2.2-PDT to reduce the number of viable tumor cells at various P2.2 concentrations and fluences of the activating light, we assessed, using qRT-PCR, the expression levels of 84 genes critically involved in the stress response of PDT-treated cells. Results showed a fluence-dependent decrease of viable tumor cells at 24 h post-PDT, with few cells that seem to escape from PDT. We highlighted following P2.2-PDT the concomitant activation of particular cellular responses to oxidative stress, hypoxia, DNA damage and unfolded protein responses and inflammation. A web of inter-connected stressors was induced by P2.2-PDT, which underlies cell death but also elicits protective mechanisms that may delay tumor cell death or even defend these cells against the deleterious effects of PDT.